Invasive Mucormycosis Induced Pneumopericardium: A Rare Cause of Pneumopericardium in an Immunocompromised Patient - Sana Khan; Muhammad Waqar Elahi; Waqas Ullah; Hafez Mohammad Ammar Abdullah; Ejaz Ahmad; Mayar Al Mohajer; Aneela Majeed (Case Reports in Infectious Diseases)
Mucor and Rhizopus cause life-threatening infections primarily involving the lungs and sinuses, which disseminate very rapidly by necrosis and infarction of the contiguous tissues. We present a case of a 64-year-old African American posttransplant patient who presented with a productive cough and weight loss. He had a past surgical history of renal transplant for renal cell carcinoma and was on dual immunosuppressive therapy, that is, mycophenolate and tacrolimus. During his hospital stay, he developed a pneumopericardium due to the direct extension of a lung lesion. The diagnosis was made by radiological imaging and PCR result which was consistent with Mucor species. He was treated with antifungal therapy. The purpose of this report is to highlight the unusual association of mucormycosis with pneumopericardium.